MODEL KEPRIBADIAN CONSCIENTIOUSNESS TERHADAP PERILAKU AKADEMIK KONTRAPRODUKTIF DENGAN PENGENDALIAN DIRI SEBAGAI PEMEDIASI - Zainnur M Rusdi (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2017)
Every individual has a different conscientiousness, this causes different reactionsof self-control and ultimately counterproductive academic behaviors that occur arealso different. The research objective to be achieved is to examine the influence ofthe nature of self-control and conscientiousness on academic behavior is counterproductive, and self-control on academic behavior is counterproductive, and examine the role of mediator variable restraint on the effect of precautionary nature of the academic behavior is counterproductive. Based on the research results that the first hypothesis which states the nature conscientiousness have a negative effect on academic counterproductive behavior is not supported. The second hypothesis which states the nature concientiousness have a positive effect on self-control is supported. The third hypothesis which states that self-control negative effect on academic counterproductive behavior is not supported. The fourth hypothesis which states restraint mediating influence of the nature of prudence on academic behavior counterproductive partially supported mediation. Someone who has a personality trait conscientiousness and low self-control tend to behave academic counterproductive.